2022
DOI: 10.1242/bio.059290
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor absence does not enhance intestinal tumorigenesis in ApcPirc/+rats

Abstract: Epidemiological observations have prompted some to posit that elevated circulating vitamin D is responsible for reduced colon cancer in individuals residing near the equator. We have previously demonstrated that vitamin D has no effect on colon cancer in two rodent models of intestinal tumorigenesis. We have now extended this line of inquiry to ask whether ablation of vitamin D receptor (VDR) affects tumorigenesis. A VDR null rat was developed using Cas9-CRISPR technology, which allowed us to investigate wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Irving et al demonstrated in both rat and mouse models of colon cancer that vitamin D supplementation does not protect against intestinal tumor development; it instead enhances tumorigenesis in the colon of the rat [ 145 , 146 ]. Moreover, the same group recently reported that loss of VDR expression alone did not induce tumorigenesis, even in animals exposed to the carcinogenic molecule sodium dextran sulfate [ 147 ]. Moreover, in Apc Pirc/+ rats, VDR loss did not enhance tumor multiplicity, growth, or progression in the colon, thus supporting previous findings that vitamin D itself does not play a role in colon cancer development or progression.…”
Section: Dysregulated Signaling Pathways In Colorectal Cancer: the Em...mentioning
confidence: 99%
“…Irving et al demonstrated in both rat and mouse models of colon cancer that vitamin D supplementation does not protect against intestinal tumor development; it instead enhances tumorigenesis in the colon of the rat [ 145 , 146 ]. Moreover, the same group recently reported that loss of VDR expression alone did not induce tumorigenesis, even in animals exposed to the carcinogenic molecule sodium dextran sulfate [ 147 ]. Moreover, in Apc Pirc/+ rats, VDR loss did not enhance tumor multiplicity, growth, or progression in the colon, thus supporting previous findings that vitamin D itself does not play a role in colon cancer development or progression.…”
Section: Dysregulated Signaling Pathways In Colorectal Cancer: the Em...mentioning
confidence: 99%
“…found that vitamin D did not affect the development of colon cancer. Through the gene knockout vitamin D receptor (VDR), it was found that the loss of VDR expression did not promote the occurrence of the tumor, and did not affect the proliferation and progression of the tumor ( 29 ).…”
Section: Application Of the Crispr/cas System In Colon Cancer Researc...mentioning
confidence: 99%
“… ABSTRACT First Person is a series of interviews with the first authors of a selection of papers published in Biology Open, helping early-career researchers promote themselves alongside their papers. Amy Irving is first author on ‘ Vitamin D receptor absence does not enhance intestinal tumorigenesis in Apc Pirc/+ rats ’, published in BiO. Amy is a research scientist in the lab of Hector DeLuca at the University of Wisconsin-Madison, USA, investigating the individual contributions of sunlight, vitamin D, calcium, and other pathway players on diseases with a location association paradigm, specifically colon cancer and multiple sclerosis.…”
mentioning
confidence: 99%